A taxonomic synopsis and morphological characterization of Myoxanthus (Orchidaceae: Pleurothallidinae) - Rojas Alvarado, Gustavo (2021)
The taxonomic history, general description and distribution are provided for Myoxanthus. Morphological characterization of the vegetative and reproductive organs is illustrated with photographs. A list of the 52 accepted species includes synonyms and distribution; most are illustrated with a flower photograph. Lectotypes for M. frutex, M. lonchophyllus, M. neillii, M. pulvinatus, M. punctatus, and M. serripetalus are designated, and a neotype is selected for M. melittanthus. Myoxanthus parvilabius is reported for the first time for Colombia. The circumscription of M. lonchophyllus is reevaluated, Pleurothallis pennellia is recognized as a distinct taxon and transferred to Myoxanthus, and Myoxanthus panamense, a new species related to M. scandens, is described from Pamana.